2019
DOI: 10.1016/j.jcjd.2018.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis-Related Diabetes Screening in Adults: A Gap Analysis and Evaluation of Accuracy of Glycated Hemoglobin Levels

Abstract: The rate of CFRD screening is suboptimal. An alternative screening algorithm using an A1C threshold of 5.5% has the potential to reduce the requirement for OGTTs by 36.7%. A1C levels cannot be used to identify impaired glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The recent study of Gilmour et al has demonstrated an alternative approach for CFRD screening in order to reduce the need for OGTT. Introducing the cutoff HbA1c value of 5.5% (36.6 mmol/mol) as an indicator for the need for further screening with OGTT could be an attractive method but has not yet been validated for the pediatric population [29] . In our study all but one of the NGT participants had their HbA1c level below this cutoff point which is promising but the cohort is too small to make any concrete assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The recent study of Gilmour et al has demonstrated an alternative approach for CFRD screening in order to reduce the need for OGTT. Introducing the cutoff HbA1c value of 5.5% (36.6 mmol/mol) as an indicator for the need for further screening with OGTT could be an attractive method but has not yet been validated for the pediatric population [29] . In our study all but one of the NGT participants had their HbA1c level below this cutoff point which is promising but the cohort is too small to make any concrete assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…Although A1C is not recommended for diagnosis of diabetes in children with cystic fibrosis or symptoms suggestive of acute onset of type 1 diabetes and only A1C assays without interference are appropriate for children with hemoglobinopathies, the ADA continues to recommend A1C for diagnosis of type 2 diabetes in this cohort (74,75). however, recent publications suggest that an A1C cut point lower than 5.4% (5.8% in a second study) would detect more than 90% of cases and reduce patient screening burden (77,78). Ongoing studies are underway to validate this approach.…”
Section: Screening and Testing For Prediabetes And Type 2 Diabetes In Children And Adolescentsmentioning
confidence: 97%
“…Ongoing studies are underway to validate this approach. Regardless of age, weight loss or failure of expected weight gain is a risk for CFRD and should prompt screening (77,78). Continuous glucose monitoring or HOMA of b-cell function ( 79) may be more sensitive than OGTT to detect risk for progression to CFRD; however, evidence linking these results to long-term outcomes is lacking, and these tests are not recommended for screening (80).…”
Section: Screening and Testing For Prediabetes And Type 2 Diabetes In Children And Adolescentsmentioning
confidence: 99%
“…The inconvenience of OGTT may contribute to poor patient uptake of CFRD screening [98][99][100]. In 2018, the Cystic Fibrosis Foundation Patient Registry reported that the average CF center was screening just 61.3% of adolescents and 32.8% of adults [100].…”
Section: Oral Glucose Tolerance Testingmentioning
confidence: 99%